1989
DOI: 10.1016/0022-0248(89)90139-5
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of silicon doping of GaAs by SiH4 and Si2H6 in atmospheric pressure metalorganic chemical vapour deposition

Abstract: Document VersionPublisher's PDF, also known as Version of Record (includes final page, issue and volume numbers)Please check the document version of this publication:• A submitted manuscript is the author's version of the article upon submission and before peer-review. There can be important differences between the submitted version and the official published version of record. People interested in the research are advised to contact the author for the final version of the publication, or visit the DOI to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

1989
1989
1998
1998

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…The free height above the susceptor, h, is about 1.6 cm. The results of growth and doping experiments in this system when the water cooler was used have been reported elsewhere [1,6,7]. When the water cooler was used, the temperature of the top wall, Ttop, was so low that elemental arsenic was deposited on the top wall.…”
Section: Methodsmentioning
confidence: 81%
See 2 more Smart Citations
“…The free height above the susceptor, h, is about 1.6 cm. The results of growth and doping experiments in this system when the water cooler was used have been reported elsewhere [1,6,7]. When the water cooler was used, the temperature of the top wall, Ttop, was so low that elemental arsenic was deposited on the top wall.…”
Section: Methodsmentioning
confidence: 81%
“…At 200 mbar, the carrier concentration level of the Si-doped GaAs is quite uniform in both cases with and without use of the air top cooler. Doping of GaAs with disilane in MOVPE or the deposition of Si from disilane have been investigated extensively [7,[12][13][14][15], although the uniformity of the carrier concentration of Sidoped GaAs was scarcely studied. It was found that the temperature dependence followed a complicated behavior, but there is a general agreement about the inverse dependence of the doping level on the growth rate.…”
Section: Si-doping Of Goasmentioning
confidence: 99%
See 1 more Smart Citation